The Impact of Training on Turnover Intention: The Role of Growth Need Strength among Vietnamese Female Employees - Nguyen, Luu Thi; Shao, Yinghong (UI Scholars Hub, 2019)
Research Aims: Incorporating theories about psychological contracts and job characteristics, this research explores the relationship between different types of training events (i.e. on-the-job versus off-the-job training) and the turnover intention of female employees. Growth Need Strength (GNS) is a personality factor that strengthens this relationship. Design/Methodology/Approach: Empirical evidence for the research was derived from a survey that collected data from 221 female corporate officers in Vietnam, followed by a hierarchical regression. Research Findings: The results suggest that GNS significantly moderates the influence of off-the-job training on turnover intention. With higher levels of GNS, women who participate in more off-the-job training and development activities provided by the company are less likely to consider leaving. This moderating effect, however, does not significantly affect the relationship between on-the-job training and turnover intention. Theoretical Contribution/Originality: The paper investigates on-the-job and off-the-job training and assesses their effects on turnover intention, with emphasis on female employees. Managerial Implications in the Southeast Asian Context: The results provide useful implications for organisational training of professional women in Southeast Asian countries, taking into consideration similarities in culture, social norms and organisational behaviour. Research Limitations and Implications: The research is limited by its sample and by a subjective self-assessment scale.